Hand gangrene after repetitive IV midazolam injections - Sapino, Gianluca; Haselbach, Celine; di Summa, Pietro Giovanni (Acta Biomedica Atenei Parmensis, 2022)
In the IV drug user (IVDU) population injection may inadvertently be intra-arterial or in the subcutaneous tissue causing a various range of complication ranging from simple cellulitis to artero-venous embolization. We present here a case of a full hand mummification and necrosis following repeated injection of chopped midazolam at the elbow, forearm and hand. A 36 year-old man presented to the emergency department with a 24 months history of slowly progressive necrosis to his right. Dry necrosis had progressively evolved into gangrene with almost spontaneous amputation at the level of the wrist. Surgical intervention was performed urgently with amputation at the proximal forearm level. No early complications were detected, and the patient did not show up at least follow-up. The present case represents an example of progressive microembolisation initially involving the hand and progressively affecting the whole forearm in an impressive mummification process over a 2-year period. Minimal but repetitive distal drug embolization can give silent and initially negligible symptoms, before clear signs of tissue sufferance are detected. When dealing with patients with IVDU history, anamnestic record of eventual use of chopped/pulverized should be performed. Careful examination of the limb should be always conducted, considering the risk of silent embolization and long term potentially devastating consequences.